2009
DOI: 10.1016/j.febslet.2009.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Rhizospheric NO interacts with the acquisition of reduced N sources by the roots of European beech (Fagus sylvatica L.)

Abstract: a b s t r a c tThe gas phase of the soil plays an important role in plant growth and development. We investigated the effect of rhizospheric NO as a signalling compound for N uptake of beech roots. Following exposure to NO, ammonium and glutamine uptake into roots were determined using 15 N-labelling, and gene expression of selected transporters was analysed by quantitative real-time PCR. Uptake of both N sources increased significantly with elevated NO concentration. However, with one exception, this increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In this context, microbial NO produced in significant amounts during nitrification and denitrification seems to be of particular significance [86]. Rhizospheric NO was shown to modulate the uptake of N compounds by tree roots [85,87,88]. Apparently, NO of microbial origin in the soil is sensed by the roots and functions as a signal that determines the competitive strength of N acquisition by the roots relative to microbial use.…”
Section: Regulation Of N Acquisition and Distribution In Treesmentioning
confidence: 99%
“…In this context, microbial NO produced in significant amounts during nitrification and denitrification seems to be of particular significance [86]. Rhizospheric NO was shown to modulate the uptake of N compounds by tree roots [85,87,88]. Apparently, NO of microbial origin in the soil is sensed by the roots and functions as a signal that determines the competitive strength of N acquisition by the roots relative to microbial use.…”
Section: Regulation Of N Acquisition and Distribution In Treesmentioning
confidence: 99%
“…Plant internal synthesis of NO is suggested to originate either from nitrate ( del Rio et al, 2004; Palavan‐Unsal and Arisan , 2009) or arginine ( Palavan‐Unsal and Arisan , 2009), but can also be induced by elicitors of defense responses ( Besson‐Bard et al, 2008). Only recently it has been shown that soil NO also influences the N uptake of the roots of deciduous and coniferous seedlings ( Simon et al, 2009, 2013), indicating the significant role of NO in plant N acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in experiments under controlled conditions, N uptake of beech and Scots pine seedlings was strongly affected by soil NO concentration, suggesting that NO is involved in the regulation of plant N uptake. However, N uptake of roots differed between species and was also influenced by soil N availability, N source, and rhizospheric CO 2 concentration ( Simon et al, 2009, 2013; Dong et al, 2015). In a study with beech seedlings, Simon et al (2009) found that high concentrations of soil NO increased the uptake of ammonium and glutamine‐N compared to ambient NO levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations